2014
DOI: 10.1182/blood-2013-10-530964
|View full text |Cite
|
Sign up to set email alerts
|

CD28-mediated pro-survival signaling induces chemotherapeutic resistance in multiple myeloma

Abstract: • CD28 delivers a pro-survival signal to MM cells via regulation of PI3K/Akt, FoxO3a, and Bim.• Blockade of CD28:CD80/ CD86 in vivo resensitizes MM cells to chemotherapy and significantly reduces tumor burden.Chemotherapeutic resistance remains a significant hurdle in the treatment of multiple myeloma (MM) and is significantly mediated by interactions between MM cells and stromal cells of the bone marrow microenvironment. Despite the importance of these interactions, the specific molecules and downstream signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 57 publications
(89 reference statements)
6
77
1
Order By: Relevance
“…These results indicated that B7-H1 expression on myeloma cells is directly associated with their aggressive characteristics, i.e., increased cell proliferation and drug resistance. Although another immune checkpoint pathway, CD28-CD86, was previously reported to prevent cell death induced by melphalan (29)(30)(31), the blockade of B7-H1 on MOSTI-1 cells using anti-B7-H1 did not affect BrdUrd incorporation and the number of apoptotic cells induced by melphalan (Fig. 1F), suggesting that MOSTI-1 cells expressed no functional receptors for B7-H1.…”
Section: Resultsmentioning
confidence: 96%
“…These results indicated that B7-H1 expression on myeloma cells is directly associated with their aggressive characteristics, i.e., increased cell proliferation and drug resistance. Although another immune checkpoint pathway, CD28-CD86, was previously reported to prevent cell death induced by melphalan (29)(30)(31), the blockade of B7-H1 on MOSTI-1 cells using anti-B7-H1 did not affect BrdUrd incorporation and the number of apoptotic cells induced by melphalan (Fig. 1F), suggesting that MOSTI-1 cells expressed no functional receptors for B7-H1.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, MRD subclones showed enhanced expression of several integrins (eg, CD11a, CD11c, CD29, CD49d, and CD49e), chemokine receptors (eg, CXCR4), adhesion molecules (eg, CD44 and CD54), CD28 (a prosurvival mediator through PC-dendritic cell interaction 39 ), and HLADR. The expression of these class of markers has been shown to be intrinsically related to different PC chemoresistant potential in vitro and in vivo, [40][41][42][43][44][45] as well as to patients' survival, [46][47][48] which would be potentially due to a stronger attachment of MRD clonal PCs to the BM stroma, which provides higher protection from 49,50 In fact, it could be hypothesized that a subset of chemoresistant MRD cells strongly attached to the stroma might be potentially underestimated in BM aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…CD28 expression in MM has been found to be associated with poor prognosis, disease progression, and resistance to chemotherapy. [15][16][17] Thus, its upregulation during the MGUS-to-MM transition may indeed reflect an escalation in the intrinsic plasma cell malignancy, meaning that oncogenic events accumulate in a clone that gains proliferative advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that DCs may promote myeloma-specific T-cell responses, 12,13 although they may also support plasma cell proliferation and survival via engagement of their CD80/86 receptors by the ligand CD28 on plasma cells. [14][15][16][17] Moreover, little information is available on DCs in the bone marrow (BM), which is the privileged site of clonal plasma cell proliferation, and therefore the main site of tumor-antigen expression.…”
mentioning
confidence: 99%